Acupressure and Therapeutic Touch in Childhood Cancer to Promote Subjective and Intersubjective Experiences of Well-being During Curative Treatment. (September 2019) - Hu, Hiroe; Shear, Deborah; Thakkar, Radhika; Thompson-Lastad, Ariana; Pinderhughes, Howard; Hecht, Frederick M; Lown, E Anne
Purpose: Acupressure and therapeutic touch may be beneficial for symptom management and increasing general well-being for children undergoing cancer treatment. Acupressure has the benefit of stimulating targeted acupuncture points while providing therapeutic touch. We sought to explore the relationship between acupressure and the experience of well-being among children being treated for cancer who received acupressure. Methods: In the Acupressure for Children in Treatment for a Childhood Cancer trial, hospitalized children received acupressure using specified acupressure points for symptom control as well as points for general well-being. Acupressure was delivered by professionals and by caregivers, following training by the professional. Qualitative data were collected through semistructured interviews with a purposive sample of professional acupressure providers (n = 3) and primary caregivers (n = 13), combined with participant observation during the acupressure intervention. Data were analyzed using grounded theory methods. Results: Analysis of provider interview, caregiver interview, and participation observation yielded 3 prominent themes: (1) well-being elicited by acupressure, (2) well-being elicited by touch, and (3) well-being experienced as relational and intersubjective. These themes, taken together, illustrate the intricate ways in which an intervention like acupressure can help alleviate the difficulties of a childhood cancer illness experience by promoting well-being in the child as well as the caregiver. Acupressure brought symptom relief, physical relaxation, and comforting touch to the child, allowing the caregiver to also feel relief and relaxation as caregiver–child experience of well-being are closely intertwined. Conclusions: Data from the 3 sources provided distinct and overlapping insights suggesting the versatile benefits of acupressure in promoting well-being during childhood cancer treatment. Professional acupressure combined with training of caregivers for childhood cancer may be a relational intervention that facilitates the experience of well-being for both the caregiver and the child.